2010
DOI: 10.1016/j.eururo.2009.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Human Prostate Fibroblasts Induce Growth and Confer Castration Resistance and Metastatic Potential in LNCaP Cells

Abstract: Background-The tumor microenvironment is important for progressive and metastatic disease.Objective-To study the hypothesis that prostate fibroblasts have differential ability to induce castration-resistant prostate cancer (PCa) and metastatic progression and whether this effect might vary depending on the zonal origin of the fibroblast.Design, setting, and participants-Human prostate fibroblasts from the peripheral (PZ), transition (TZ) and central (CZ) zones of radical prostatectomy specimens (n = 13) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…In contrast, patients with advanced prostate cancer often develop osteoblastic bone metastasis. Both primary prostate cancer CAFs and bone stroma have been known to induce prostate cancer growth and confer castration resistance and metastatic potential (5, 32–34). However, the role of TGF-β signaling in osteoblastic lesion development in bone remains largely unclear, further the effect of TGF-β signaling in the primary site on eventual prostate cancer bone metastasis is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, patients with advanced prostate cancer often develop osteoblastic bone metastasis. Both primary prostate cancer CAFs and bone stroma have been known to induce prostate cancer growth and confer castration resistance and metastatic potential (5, 32–34). However, the role of TGF-β signaling in osteoblastic lesion development in bone remains largely unclear, further the effect of TGF-β signaling in the primary site on eventual prostate cancer bone metastasis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastatic studies have generally focused on examining the interactions of cancer cells with the bone microenvironment due to a lack of appropriate animal models and cells that recapitulate the whole process of metastasis from the orthotopic site. Recently, it has been appreciated that the primary tumor microenvironment not only provides fertile soil for cancer growth but also exerts dominant influences that trigger changes in cancer cells, conferring their selective growth and survival in metastatic sites (57). …”
Section: Introductionmentioning
confidence: 99%
“…The specific nature of the human PCa stromal phenotype has been shown to be an independent clinical prognostic marker (26,27), underlining the importance of paracrine interactions in human disease. The prostate tumor microenvironment is complex, including cells of many different lineages (28)(29)(30)(31). These include, but are not limited to, smooth muscle, various types of fibroblasts, senescent stromal cells, nerves and blood vessels and a wide variety of immune and inflammatory cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings associated with CAF induction and hormone-stimulated growth have also been reported (Hayward et al 2001). In addition, Thalmann et al (2010) have demonstrated the ability of CAFs to promote castration resistance in an LNCaP model, indicating that the CAFs contribute to lethal disease. We demonstrated that distinct populations of stromal cells reside in the prostate tumor microenvironment relative to stromal cells from normal prostate peripheral zone tissue and, more importantly, relative to stromal cells in BPH tissue (Barclay et al 2005).…”
Section: Cancermentioning
confidence: 99%
“…1, a schematic of androgen-regulated signaling pathways in prostate cancer is shown. CAFs from both the peripheral and transitional zones can induce a metastatic phenotype in the normally non-metastatic LNCaP cell line in vivo, but the mechanisms are unclear (Thalmann et al 2010). Reactive stroma is also a major problem in prostate cancer progression.…”
Section: Cancermentioning
confidence: 99%